PENGEMBANGAN MODUL PRAKTIKUM FISIKA DASAR I BERBASIS KETERAMPILAN PROSES SAINS - Abdul Hamid; Muhammad Syukri; Putri Shalina (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2022)
AbstractThe purpose of this study is to determine the feasibility and response of student to the basic physics practicum module based on science process skills. This research methodology is a development technique that combines an R&D research design with an ADDIE development pattern. The participants in this study were physics education students enrolled in basic physics practicum course, 2021/2022. This study employs a non-test instrument that consist of a module validation sheet, an observation sheet, and a student response questionnaire. The data in this study was analyzed using quantitive and qualitative descriptive analysis. The data analysis result revealed that the physics practicum module based on science process skills was designed to obtain valid criteria with an average result of 3.3 in material and media aspect, and the result of student responses obtained very interesting criteria.Keywords: Practicum Module, Basic Physics I, Science Process Skills